Copper-Mediated Synthesis of Aryl α-Keto Amides from Epoxide Derivatives - Liu, Fenghua; Cui, Yunjian; Dong, Yi; Xu, Heng (Synlett, 2020)
A novel CuII-mediated synthesis of aryl α-keto amides from epoxide derivatives is reported. This transformation was conducted by using O2 as a green oxidant that meets the requirements of sustainable chemistry.
Keywords: copper catalysis; keto amides; epoxides; green chemistry